Coronary Subclavian Steal Syndrome Unamenable to Angioplasty Successfully Managed with Subclavian-Subclavian Bypass - Saad Tariq; Swosty Tuladhar; Edward Wingfield; Honesto Poblete (Case Reports in Vascular Medicine)
Purpose. Coronary-subclavian steal syndrome (CSSS) is defined as a reversal of flow in a previously constructed internal mammary artery (IMA) coronary conduit, producing myocardial ischemia. We present a case of CSSS which could not be ameliorated with endovascular therapy and necessitated a subclavian-subclavian bypass. Case Report. 80-year-old Caucasian male with history of CABG presented with syncope. He had absent left-sided radial pulse with blood pressure being 60/40 on left arm and 130/80 on the right. He underwent cardiac catheterization for NSTEMI which showed patent left internal mammary artery graft to left anterior descending coronary artery with retrograde flow, and diagnosis of coronary subclavian steal syndrome was made. Complete occlusion of proximal left subclavian artery was identified. Percutaneous angioplasty failed because of calcified plaque causing 100% occlusion. Carotid doppler showed bilateral carotid artery disease. He finally underwent subclavian-subclavian bypass which resolved his condition. Conclusion. Subclavian-subclavian bypass is a successful alternative to carotid-subclavian bypass for management of CSSS especially with concomitant critical carotid artery atherosclerotic disease.